Islamic Education in Preserving Mental Health Based on the Qur’an in the Contemporary Era - Ernawati Sulhatul Imamah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic education is a holistic framework grounded in the Qur’an and Hadith, aiming not only to transmit knowledge but also to cultivate values, ethics, and spiritual awareness. Mental health—defined as the optimal functioning of one’s emotional and psychological potential—is increasingly relevant in educational contexts. Integrating Qur’anic principles may offer meaningful responses to contemporary mental health issues such as anxiety, stress, low self-esteem, and emotional imbalance. This study employed a qualitative library research method, using textual analysis of books, scholarly journals, and classical Islamic sources. Content analysis was applied to identify Qur’anic verses and their interpretations (tafsīr) that address aspects of mental health. The findings reveal that Qur’anic values—such as ṣabr (patience), tawakkul (trust in God), dhikr (remembrance of God), prayer, gratitude, and inner peace—serve as key psychological resources. These principles contribute to emotional regulation, resilience, and self-awareness, offering spiritual and practical strategies for mental well-being. Islamic education, when integrated with Qur’anic spiritual teachings, can significantly support students’ mental health. The study suggests that schools implement Qur’an-based counseling programs and embed Islamic psychological values within the curriculum. Additionally, training for Islamic education (PAI) teachers should include components of Qur’anic psychology to enhance their role in guiding students through emotional challenges.